The incidence and cost of job loss in the Ukrainian labor market - Hartmut Lehmann; Norberto Pignatti; Jonathan Wadsworth (W.E. Upjohn Institute for Employment Research, 2005)
We examine the effects of economic transition on the pattern and costs of worker displacement in Ukraine, using the Ukrainian Longitudinal Monitoring Survey (ULMS) for the years 1992 to 2002. Displacement rates in the Ukrainian labor market average between 3.4 and 4.8 percent of employment, roughly in line with levels typically observed in several Western economies, but considerably larger than in Russia. The characteristics of displaced workers are similar to those displaced in the West, in so far as displacement is concentrated on the less skilled. Around one third of displaced workers find re-employment immediately while the majority continues into long-term non-employment. The wage costs of displacement for the sub-sample of displaced workers do not seem to be large. The main cost for displaced workers in Ukraine consists in the extremely long non-employment spell that the average worker experiences after layoff.
Keywords: J64; J65; P50; 330; Displaced workers; Labor markets in transition; Ukraine; Kündigung; Arbeitslosigkeit; Arbeitsmobilität; Lohn; Übergangswirtschaft; Ukraine